Sophie Assiniway / Grace Chandler Horn - Horn, Grace Chandler, photographer. (William L. Clements Library, 1900)
Full length portrait of Sophie Assiniway wearing western clothing standing with back to camera in pumpkin patch near home in Middle Village, Michigan. Lacking mount.; Blindstamp: Grace Chandler Horn.; Contemporary inscription on verso: Fasquelle.; Title devised by cataloger.; "Sophie Assiniway" variant personal names: Sophia Assinaray, Sophia Pagowiah, Sophie Assinaray, Sophie Assinaway.; "Ottawa Indians" variant names: Anishinaabe, Odawa Indians, Outaouak Indians, Tawa Indians.